The role of cybersecurity in addressing the rise on cybercrime activities - Mohd Khairul Amri, Kamarudin; Norfatihah, Haron; Mohd Armi, Abu Samah (2020)
Innovations and technological advances have resulted in several web-based products. Among them are social networking sites that are dominating internet usage among users. This article discusses many types of cybercrime that are prevalent today, namely, hacking, cyber fraud, spamming and cyber harassment. This article review was conducted as a systematic using computer based electronic search to access all journals related for cyber crime by using Google Scholar and Researchgate to collect the information for get the high impact on this article. The objective of this article is to discuss about CyberSecurity is a service created by the Ministry of Technology and Innovation of Malaysia that receives complaints from users who are victims of cybercrime and then the body will make statistics based on complaints received. Malaysia use the MyCERT service created by the Ministry of Science and Technology to receive any complaints related to this cybercrime activity. Based on the statistic in MyCERT type of cybercrime like fraud had the highest cases that have been recorded by MyCERT. Recorded by BruCERT from 2011 to 2015, with 61% of Malicious Software activities recording the highest percentage compared to cyber harrasment, website, spam and scam. In addition, it was followed by cyber harassment of 31%, website 5% and scam 3%. In this case, shows in Brunei also experience similar criminal activity in Malaysia. The support and responsibility of certain parties and societies play an important role in providing awareness and exposure to cybercrime. IT education is also able to curb issues related to cybercrime as a precautionary measure for students and adolescents to avoid becoming victims of cybercrime.